2012
DOI: 10.1038/pcan.2012.47
|View full text |Cite
|
Sign up to set email alerts
|

Association between DNA methylation of HSPB1 and death in low Gleason score prostate cancer

Abstract: Background:Heat shock protein 27 (Hsp-27) encoded by gene HSPB1 is a critical regulator of the behavioral phenotype of human prostate cancer (PCa) cells, enhanced expression being associated with highly aggressive disease and poor clinical outcome. In contrast, the protein is not expressed in PCas of low malignant potential. To gain insight into the mechanism regulating its expression, we tested the hypothesis that differential methylation of CpG islands within HSPB1 controls transcription and subsequent trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…These studies have identified new potential tumor markers including methylation of PITX2 , HOXD3 , APC , TGFβ2 , RASSF1A , ANEP , PCDH10 , ZNF132 , TDRD1 , AOX1 , C1orf114 , GAS6 , HAPLN3 , KLF8 , MOB3B , CCND2 , PTGS2 , RARB , SRD5A2 and CYP11A1 , thus emerging as new predictors of BCR particularly in high-risk clinically localized disease. Also the level of methylation of HSPB1 , the gene encoding heat shock protein-27 [25], and Ras association (RalGDS/AF-6) domain family member 1 ( RASSF1 ) [26] associate to death in low Gleason score PCa.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have identified new potential tumor markers including methylation of PITX2 , HOXD3 , APC , TGFβ2 , RASSF1A , ANEP , PCDH10 , ZNF132 , TDRD1 , AOX1 , C1orf114 , GAS6 , HAPLN3 , KLF8 , MOB3B , CCND2 , PTGS2 , RARB , SRD5A2 and CYP11A1 , thus emerging as new predictors of BCR particularly in high-risk clinically localized disease. Also the level of methylation of HSPB1 , the gene encoding heat shock protein-27 [25], and Ras association (RalGDS/AF-6) domain family member 1 ( RASSF1 ) [26] associate to death in low Gleason score PCa.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of the studies focusing on the prognostic value of methylation have used time to biochemical recurrence after surgical treatment as the primary surrogate end point, which does not accurately estimate the potential of the cancer in terms of risk of death if left untreated. We recently reported the prognostic value of methylation of HSPB1 to predict men at risk of dying from PCa in a watchful waiting cohort [15]. In the current casecontrol study, we used the same cohort but focused on patients with localized PCa of Gleason score ≤7 and investigated if methylation of additional genes can predict poor survival.…”
mentioning
confidence: 98%
“…A growing body of evidence indicates that methylation has potential to improve the sensitivity for PCa diagnosis [14]. In addition, it has been suggested that DNA methylation assays could be prognostic and complementary or perhaps an alternative to other prognostic tests such as the CCP score, immunohistochemisty or other kinds of approaches [9,15,16]. Methylation assays have desirable features such as robust measurement of stable DNA and the potential of inexpensive assays [17] tools for predicting aggressive PCa [18].…”
mentioning
confidence: 99%
“…DNA methylation is a mitotically transmitted epigenetic motif that can be measured with good accuracy in tissue biopsies, exfoliated cells, blood and other fluids and can be related to exact physical locations in the genome; this feature lends itself more readily to medical diagnostics. Clinically relevant methylation changes are known in many human cancers such as cervix, prostate, breast, colon, bladder, stomach, oesophagus and lung cancers [1,[10][11][12] . Differential methylation may have a central role in the development and outcome of most if not all human malignancies.…”
Section: The Interface Of Epigenetics and Geneticsmentioning
confidence: 99%